PERAN LITERASI KEUANGAN DALAM MEMEDIASI PENGARUH PENGGUNAAN DOMPET DIGITAL TERHADAP PERILAKU INVESTASI DAN PENGELOLAAN KEUANGAN PRIBADI - Juniawan, Farhan Murti (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
personal financial management, with financial literacy acting as a mediating variable. In an increasingly complex digital era, the adoption of financial technologies such as e-wallets has significantly transformed individual consumption patterns and financial decision-making processes. Using a quantitative approach, this research involved respondents from the productive age group who actively use e-wallets and engage in financial management activities. The study underscores the critical role of financial literacy in fostering responsible financial behavior and recommends strengthening financial literacy as a strategic effort to enhance the effectiveness of digital financial technology adoption.